An intersectional approach to climate justice activism - Maseti, Thandokazi (PINS-Psychology in Society, 2022)
Vanessa Nakate (2021). A Bigger Picture: My Fight to Bring a New African Voice to the Climate Crisis. Pan Macmillan. 304 pages. ISBN 13: 9780358654506 Vanessa Nakate’s A Bigger Picture is an informative, eye-opening, and brave book that offers us a voice often missing in environmental and climate change scholarship. Nakate, a young woman climate change activist based in Kampala, Uganda, begins the book by reflecting on the morning of January 2020 in Davos, Switzerland. Nakate was part of the press conference at the World Economic Forum and had taken pictures with four other young climate activists (all from Europe). At the start of the book, she reflects on finding out that she had been cropped out of a photo that was published in the media. Only a piece of her coat was left to confirm to herself that this was clearly the photo she had been in. In the photo, Vanessa was the only black woman and the only African. She begins the book by reflecting on how being cropped out felt like an entire continent had been cropped out and silenced. Vanessa Nakate uses this moment of being cropped out to bring us this book; she explains: “being cropped out of that photo changed the course of my activism and my life. It reframed my thoughts about race, gender, equity and climate change justice, and it led to the words you are now reading.” (Nakate, 2021: 3).